Application of Microtremor Analysis for Soil Characterization in Urban Areas - Hoh, Kai Sheng; Lee, Hong Shen; Hisyam, Muhammad Noor; Sapitri, Sapitri; Surol, Salihah (Journal of Soil, Environment & Agroecology, 2025)
Landslides pose a significant threat to safety and infrastructure in Malaysia, exacerbated by its tropical climate and rapid urbanization. Traditional assessment methods are often impractical for frequent monitoring due to their destructive nature. This study explores the application of the Horizontal-to-Vertical Spectral Ratio (HVSR) method, integrated with Multichannel Analysis of Surface Waves (MASW), for subsurface characterization and slope stability evaluation. Key findings include shear wave velocity profiles from MASW (180–250 m/s at 0–10 meters depth) and HVSR (147 m/s at 0–5 meters), which are crucial for assessing soil stiffness and seismic hazards. The subsurface was stratified into four zones based on Vs and SPT-N values, providing insights into soil strength and compaction. The HVSR analysis revealed fundamental resonance frequencies indicative of subsurface layer thickness and stiffness. This study validates the effectiveness of HVSR in complementing traditional methods, offering a rapid and cost-effective solution for landslide risk management. The results contribute significantly to enhancing geotechnical engineering practices in Malaysia and similar regions, highlighting the potential for widespread adoption of non-destructive techniques in landslide risk assessment and mitigation strategies.